2008
DOI: 10.1577/h06-031.1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Vibrio harveyi OmpK* and GAPDH* Genes and Their Potential Application as Vaccines in Large Yellow Croakers Pseudosciaena crocea

Abstract: Vibrio harveyi is a causative agent of vibriosis in the large yellow croaker Pseudosciaena crocea and causes severe losses to the aquaculture industry in China. The vaccines based on the outer membrane proteins (OMPs) of the pathogens are considered to be the optimum intervention for this disease. In this study, two V. harveyi OMP genes, OmpK* and glyceraldehyde-3-phosphate dehydrogenase (GAPDH*), were cloned, sequenced, and characterized. The recombinant proteins (r-OmpK and r-GAPDH) were expressed by the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The amino acid sequence of OmpK is much similar to nucleoside‐specific channel‐forming OMP (Tsx) of enteric bacteria, which suggests its important biological function for the organism. With respect to the immunogenicity, the protective immunity induced by vaccination of V. harveyi OmpK in large yellow croaker has already been reported (Zhang and others 2008). The ompW and the ompV are related to osmoregulation in V. parahaemolyticus and V. alginolyticus , and appear immunogenic in V. cholera e (Xu and others 2004, 2005; Nandi and others 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequence of OmpK is much similar to nucleoside‐specific channel‐forming OMP (Tsx) of enteric bacteria, which suggests its important biological function for the organism. With respect to the immunogenicity, the protective immunity induced by vaccination of V. harveyi OmpK in large yellow croaker has already been reported (Zhang and others 2008). The ompW and the ompV are related to osmoregulation in V. parahaemolyticus and V. alginolyticus , and appear immunogenic in V. cholera e (Xu and others 2004, 2005; Nandi and others 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Although outer membrane proteins of bacteria have been regularly reported as antigens for vaccine development [24][25][26] other proteins such as pyridoxal phosphate biosynthetic protein in Helicobacter pylori [27], glyceraldehyde-3-phosphate dehydrogenase (GAPDH), haemolysin HL1 and protease chaperon DegQ in V. harveyi [28,29] were also reported to be suitable candidate antigens for vaccine recently. The fish immunized with DLD also had significantly raised specific antibody levels when compared to controls suggesting that the vaccine stimulated a specific memory response in the fish which conferred protection when challenged.…”
Section: Discussionmentioning
confidence: 99%
“…Several V. harveyi recombinant subunit vaccine candidates have been reported by different research groups and demonstrated to be effective in laboratory trials. These protein-based vaccines include the outer membrane protein OmpK, glyceraldehyde-3-phosphate dehydrogenase, and haemolysin [28][29][30]. In addition, our recent study has identified a chaperon protease from V. harveyi and found it highly immunoprotective when used as a secreted vaccine [31].…”
Section: Introductionmentioning
confidence: 99%